Determining the dynamic characteristics of hydraulic excavators - Lazarević, Olgica Ž.; Lazarević, Boro M. (Vojnotehnički glasnik / Military Technical Courier, 2017)
This paper deals with the research into the dynamic characteristics of hydraulic excavators i.e. natural frequencies and movements. The way hydraulic excavators work is described by the mathematical model of six generalized coordinates based on the Lagrange equations of the second kind. The obtained mathematical model of the excavator system represents the system of six nonlinear, nonhomogeneous differential equations of the second kind. By simulating real parameter values, we managed to obtain the functions of movement and their natural frequency changes within the allowed degrees of freedom, making it possible to examine the nature and intensity of those movements and the impacts of these parametres on excavator operators as well as on excavator construction optimisation.